Penerapan Sanksi Adat dalam Penyelesaian Tindak Pidana di Desa Golo Poleng Kabupaten Manggarai Barat - Elfrida Diana Salut; Karolus K. Medan; Ngongo Dede (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to find out the process of applying customary law sanctions of Wunis Peheng in resolving the criminal act of persecution committed by police and TNI personnel against a resident in Golo Poleng village, Ndoso District, West Manggarai Regency. In addition, it also aims to find out whether the customary sanction of Wunis Peheng in resolving the crime of persecution can provide a sense of justice for residents. This research is categorized as empirical juridical research. The empirical juridical approach aims to analyze problems using legal materials related to problems that occur in the field. Data collection techniques are carried out by means of observation, interviews, and documentation studies. The data that is processed and analyzed based on the formulation of the problem that has been determined is then presented in a qualitative descriptive manner. The results of this study show that there are several stages in the process of applying customary sanctions of wunis peheng in the settlement of criminal acts of persecution, namely reporting cases of persecution to Tu'a Golo, summoning the parties involved in the persecution case, examination and verdicts of customary institutions, handing over Wunis Peheng from the perpetrator, Saying Traditional Prayers, Slaughtering ela (pigs). And several dimensions of justice in the provision of customary law sanctions, namely the rights of victims are fulfilled, restorative justice, and active participation of the community.